2013
DOI: 10.1103/physrevd.87.067504
|View full text |Cite
|
Sign up to set email alerts
|

Modified-gravity wormholes without exotic matter

Abstract: In this paper, we develop an iterative approach to span the whole set of exotic matter models able to drive a traversable wormhole. The method, based on a Taylor expansion of metric and stress-energy tensor components in a neighbourhood of the wormhole throat, reduces the Einstein equation to an infinite set of algebraic conditions, which can be satisfied order by order. The approach easily allows the implementation of further conditions linking the stress-energy tensor components among each other, like symmet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
243
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 345 publications
(244 citation statements)
references
References 28 publications
0
243
0
1
Order By: Relevance
“…Here, at the bifurcation frequencies ω crl and ω cru the symmetric solutions indeed exhibit a zero mode, which then turns into a second unstable mode in the parameter space where the asymmetric solutions exist. For the asymmetric solutions stability could possibly be achieved by removing the phantom field and modifying gravity instead [35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Here, at the bifurcation frequencies ω crl and ω cru the symmetric solutions indeed exhibit a zero mode, which then turns into a second unstable mode in the parameter space where the asymmetric solutions exist. For the asymmetric solutions stability could possibly be achieved by removing the phantom field and modifying gravity instead [35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that higher-dimensional cosmological wormholes [9] and wormholes in modified gravity, involving higher order curvature invariants, can satisfy the energy conditions [10][11][12][13][14], at least at the throat. In fact, in modified gravity, it was shown that matter threading the wormhole throat can be imposed to satisfy all of the energy conditions, and it is the higher order curva-ture terms, which may be interpreted as a gravitational fluid, that support these nonstandard wormhole geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Static and spherically symmetric black hole solutions in F(R) have been found [35][36][37] in the last decade. Traversable wormholes in F(R) were also studied in recent years [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%